895 Effect of 4% Chlorhexidine Cord Cleansing on Colonisation and Bacterial Count in Hospital Born Neonates. (October 2012) - Nangia, S; Saili, A; Madhesiya, S; Dhingra, P; Dhingra, U; Dutta, A; Menon, VP; Black, RE; Gupta, S; Ahmed, A; Sazawal, S
Abstract : Background: Infections in new-borns are the single most important cause for neonatal mortality in developing countries. Of topical antiseptics chlorhexidine has shown potential as an effective cord care agent. Results from randomized double-blind trials examining the effect of chlorhexidine in Asia have been encouraging. A 4% chlorhexidine solution is not comercially available we contracted Galantic Pharma to prepare supplies for two large clinical trials in Africa. This study aimed to evaluate the effect this 4% chlorhexidine solution on the colonization and colony counts in hospital born infants. Methods: Newborns (n=247) from normal deliveries at a hospital in New Delhi were randomly assigned to one of three groups chlorhexidine, placebo or dry cord care. Swab samples were used to collect smear samples before, after 2hrs and 48hrs of application of chlorhexidine and at same times from the dry cord group. All swabs were analysed for growth and colony counts. Results: The overall baseline positivity was 20% (50 of 247 swabs). Chlorhexidine reduced colonisation and bacterial counts in both (2hr and 48 hr) samples. As compared to placebo and dry cord, the reduction in positivity in chlorhexidine group in 2-hour samples was 80% [odds ratio of 0.20, p=0.001 and odds of 0.19, p=0.00 respectively]. In 48-hour post intervention, chlorhexidine significantly reduced colonisation in comparison to placebo [difference in mean of –1.01, p=0.006] and dry cord [difference in mean –1.16, p=0.004]. Conclusion: Cord cleaning with 4% Chlorhexidine soon after birth reduces colonisation as well as density of pathogens significantly.